Abuse of Authority by ASN and State Officials Reviewed from Administrative Law - Bisara, Maria Theresia Nisa; Suyatna, I Nyoman (Peneliti.net, 2025)
The purpose of this study is to examine the abuse of authority committed by the State Civil Apparatus (ASN) and state officials who hold administrator positions in government, as well as to find out their accountability based on Law Number 5 of 2014 which regulates the State Civil Apparatus (ASN). This research uses normative legal research methods with a qualitative descriptive approach. Data is obtained through analysis of primary legal materials, such as Law Number 5 of 2014, and secondary legal materials, such as related literature and journal articles. The results show that abuse of authority can occur in various forms, including actions that are contrary to personal or public interests. Law Number 5 of 2014 clearly regulates the accountability of ASN and state officials related to abuse of authority, by providing administrative sanctions and disciplinary action. In conclusion, protection of integrity and fairness in state administration is essential to prevent abuse of authority in the future.